Atuação do centro de cultura negra - negro Cosme (CCN-NC) na cidade de Imperatriz – Maranhão - SILVA, Maria Zilma Rodrigues (2022)
The title of this research is Actions of the Black Culture Center - Negro Cosme (CCN-NC) in the City of Imperatriz, Maranhão. Our aim is to know the history of this non-profit civil society entity, which develops actions aimed at raising awareness and citizenship of black men and women in different spaces of society with the purpose of combating racism. Thus, this study brings the following guiding questions: What is the contribution of the Black Movement in my life and in my academic training? It is about my life story, my construction process as a researcher of the Black Movement. What is the historical panorama of the Brazilian Black Movement? It refers to how the black resistance was formed before the abolition of slavery, the formation and phases of the Black Movement in Brazil and in Maranhão. How does the Black Culture Center - Negro Cosme (CCN - NC) function in the city of Imperatriz, Maranhão? Regarding the activities developed by the Black Culture Center - Negro Cosme throughout its existence and the challenges to continue with this work to combat racial discrimination, where the initial search was to identify the contribution of the Black Movement in my life and in my academic training; then, to analyze the historical panorama of the Brazilian Black Movement; and finally, to describe how the Black Culture Center - Negro Cosme (CCN-NC) operates in the city of Imperatriz, Maranhão. To that effect, our research is based on the contributions of Nascimento (1978); Nascimento (2006); Almeida (2018); Gonzalez (1984); Santos (1984); Gomes (2012), Ribeiro (2019), Kilomba (2019), among other authors and several works corresponding to our proposal. To achieve our results, the chosen methodological path was the autobiographical research history of the researcher's life, and also through documentary research in oral, written and audiovisual sources such as the Prosa de Pret@ Program, Statute, Regiment of the Balaiada Publisher, various types of documents for information collection. The qualitative approach focused on the dynamics of social relations, seeking to understand behaviors with a decolonial focus, that is, in the search for a decolonization of knowledge, since the way in which the colonization of America and Brazil was carried out left deep marks that reflect on behavior, in thought and education, given that in Brazil the Eurocentric imposition silences black people in their ways of producing knowledge, the domination of colonial thought reflects to the present day. The relevance of this research is social, as it is centered on the perspective of transformation in society, in the way of organizing knowledge, taking into account different voices and learning processes. From this perspective, we seek to describe what the CCN-NC is, an entity that develops activities on a voluntary basis and that has contributed to the black people in the society of Imperatriz. As a product of this research, we present an informative booklet on the performance of the Black Culture Center - Negro Cosme, aiming with this to contribute so that more people, black people, students, teachers and the community in general learn how the Black Culture Center – Negro Cosme has been functioning in the last twenty years to fight racism.